APPLICATION OF GDS AS SCHOOL CULTURE FOR STRENGTHENING SCHOOL STUDENT CHARACTERS IN JUNIOR HIGH SCHOOL 19 BANDUNG - Lestari, Maulid Dea (Universitas Pendidikan Indonesia, 2018)
This research is motivated by researchers' interest in the cultural program of the 19th Bandung Middle School, namely GDS (Student Discipline Movement). The factor that caused the birth of the GDS was due to the school's concern for the lack of attention of students in the prevailing discipline in the school. So that the school creates a school culture in the form of activities that empower students with the hope that students can train character education especially in discipline in carrying out school rules. Therefore, this research was conducted with the aim to find out several things including the first driving factors for the birth of GDS, secondly the description of GDS activities, the three efforts of the school in facing the discipline characteristics of students, the four impacts of GDS on the discipline character of students in carrying out the order. This study uses a qualitative approach with descriptive methods of data collection carried out through study documentation, observation and interviews. Based on the results of the study, it was found that the driving factor for the birth of GDS activities in 19th Public High School in Bandung was due to the restlessness of the surrounding community towards the behavior of students. Meanwhile, GDS has become an institutionalized activity in upholding school discipline in SMP Negeri 19 Bandung. The efforts of the school in dealing with the disciplinary characteristics of students at 19 Bandung Junior High School by involving students through GDS activities to discipline students so that they can adhere to school discipline. The impact of the GDS can reduce student violations even though they have not been effective due to the lack of support from the school.Â Â